Corporate Social Responsibility and Customer Loyalty: A Case of MTN Ghana - Nikoi Kotey, Cephas (UniMAC - GIJ, 2017)
This research work focuses on Corporate Social Responsibility (CSR) as a Public Relations intervention, and its 'role in enhancing Customer Loyalty. It sought to find out if customers stay with MTN because of Corporate Social Responsibility Initiatives and to determine if Customers stay loyal to MTN regardless of Service Level problems. The study used face-to-face semistructured interviews to collect data from a sample selected purposively and conveniently. Participants showed generic knowledge and understanding of Corporate Social Responsibility (CSR) as developmental projects undertaken by corporate organisation. Participants attributed their choice of MlN over other telecommunications companies to wide network coverage, and reasonable service charges, in relation to phone calls and internet service. With regards to loyalty decisions, more claimed they will patronise' MTN and use its services in the future" but not because of their CSR activity. The interview indicates that participants are interested in getting value for the monies they expend on the products of MTN, or some kind of satisfactory quality of service, hence their decision on brand patronage due to great service qUality. This study revealed that in as much as CSR somewhat courts an amount of customer loyalty, most customers show loyalty based on quality of service in tenns of accessibility, costs, proximity, speed and effectiveness et cetera. Customers expect to have value for their monies. There is the need for a large population study for quantitative data on this important issue of CSR and Customer Loyalty. Also, service quality should be a priority for enhancing customer loyalty. CSR activities aimed at individuals, with notable benefits that these individuals can solidly lay claim to, should be captured in the general CSR plan of corporate organisations like MTN.
Thesis